Endoscopic Retrograde Cholangiopancreatography Using a Dual-Lumen Endogastroscope for Patients with Billroth II Gastrectomy - Wei Yao; Yonghui Huang; Hong Chang; Ke Li; Xuebiao Huang (Gastroenterology Research and Practice)
Objective. To evaluate the safety and efficacy of a dual-lumen forward-viewing endoscope for ERCP in patients with prior Billroth II gastrectomy. Methods. The records of 46 patients treated with ERCP by a dual-lumen forward-viewing endoscope after Billroth II gastrectomy from 2007 to 2012 were reviewed. Results. The success rate of selective cannulation was 82.6% (38/46). Of the 38 cases with successful selective cannulation, endoscopic sphincterotomy was achieved in 23 cases by placing the needle knife through the 2nd lumen, while endoscopic papillary balloon dilatation was conducted in the other 15 cases. Of the 8 failed cases of selective cannulation, 6 had failed afferent loop intubation, and 3 of these 6 patients had Braun’s anastomosis. The safety and efficacy of catheter-assisted endoscopic sphincterotomy were increased by placing the needle knife through the 2nd lumen without altering the conventional endoscopic sphincterotomy procedure. Conclusions. A dual-lumen forward-viewing endoscope can be safely and effectively used to perform ERCP in patients with a Billroth II gastrectomy, except for patients with additional Braun’s anastomosis.